Disease-Free Survival at 2 and 3 Years is a Significant Early Surrogate Marker Predicting the 5-Year Overall Survival in Patients Treated with Radical Cystectomy for Urothelial Carcinoma of the Bladder: External Evaluation and Validation in a Cohort of Korean Patients - Kim, Hyung Suk; Jeong, Chang Wook; Kwak, Cheol; Kim, Hyeon Hoe; Ku, Ja Hyeon (Frontiers in Oncology, 2015)
Purpose: We aimed to externally validate the association of 2- and 3-year disease-free survival with 5-year overall survival in patients treated with radical cystectomy for urothelial carcinoma of the bladder. Materials and Methods: We reviewed the clinical data of 422 patients who underwent radical cystectomy for urothelial carcinoma of the bladder in our institution between 1991 and 2012. Survival curves were plotted with the Kaplan–Meier method. The Kappa statistic and Kendall tau-b test were used to assess the agreements between 2- and 3-year disease free survival and 5-year overall survival. Results: In the entire study population, 2- and 3-year disease free and 5-year overall survival rates were 76.4%, 71.5%, and 67.4%, respectively. All Kappa and Kendall’s tau-b test values for agreements between 2- and 3-year disease free and 5-year overall survival were more than 0.40, indicating moderate agreement for all patients and in each patient subgroup selected according to specific variables (all p values <0.05). Kaplan–Meier analysis for disease free survival and Cox-proportional hazard models for landmark analysis at each time point indicated that most recurrences occurred within 3 years after surgery. The 5-year overall survival rates of patients who were recurrence free at each time point gradually increased to more than 95% in an extended recurrence-free interval of 12–36 months. Conclusions: Our external validation results support the existing finding that 2- and 3-year disease free survival can be a valid early surrogate end point to predict 5-year overall survival after radical cystectomy in patients with urothelial carcinoma of the bladder.